2018
DOI: 10.1186/s12983-018-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

A consistent long-lasting pattern of spatial variation in egg size and shape in blue tits (Cyanistes caeruleus)

Abstract: BackgroundInterspecies variation in avian egg shape and size is understandable in terms of adaptation, allometry and phylogeny. Within-species variation in egg properties influences offspring fitness and can be explained by differences in allocation of resources into reproductive components of life history in mulidimensionally variable environments. Egg size is inherently traded-off with clutch size, which may also be true of egg shape in some cases. We investigated long-term variation in egg shape and size be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…According to Hõrak et al (1995), "being hatched from a large egg could potentially be beneficial of the laying female, however, high investment into egg quality (size) might conflict with her own energetic demands and willingness to produce more offspring". Studies have found negative (Martin et al 2006, Bańbura et al 2018, positive (Aslan & Yavuz 2010, Dolenec 2016) and no significant correlations (Dolenec 2011, Bao et al 2020 between egg size and clutch size. Negative relationships between egg volume (or egg mass) and clutch size is consequence of compromise between egg size and clutch size with females laying numerous small or few large eggs (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…According to Hõrak et al (1995), "being hatched from a large egg could potentially be beneficial of the laying female, however, high investment into egg quality (size) might conflict with her own energetic demands and willingness to produce more offspring". Studies have found negative (Martin et al 2006, Bańbura et al 2018, positive (Aslan & Yavuz 2010, Dolenec 2016) and no significant correlations (Dolenec 2011, Bao et al 2020 between egg size and clutch size. Negative relationships between egg volume (or egg mass) and clutch size is consequence of compromise between egg size and clutch size with females laying numerous small or few large eggs (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, advances in the ease of making accurate measurements of egg shape and the ability to conduct large-scale comparative analyses have led to a renewed effort to understand what factors drive variation in egg shape between species (Duursma et al, 2018; Montgomerie et al, 2021; Nagy et al, 2019; Shatkovska et al, 2018; Stoddard et al, 2017). Despite the number of studies of egg shape, relatively few have examined variation in shape between populations, between individuals, or within individuals of the same species (but see Adamou et al, 2018; Bańbura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A complete understanding of egg shape variation will require a scale-dependent framework (Agrawal, 2020) that makes predictions that explicitly consider the scale, based on an understanding of the mechanism(s) involved. Analyses at these different levels are complementary, rather than contradictory (Stoddard et al, 2019), but at present, very few studies provide even descriptive data on correlates of variation in egg shape within species or individuals (but see Adamou et al, 2018; Bańbura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation